PANDANGAN HERMENEUTIKA TERHADAP KASUS MEREK DAGANG GOTO VS GoTo - Imelda Martinelli; Ivan Richard Sugiarto; Ernita Dewy Hartono (UNES Law Review, 2023)
Hermeneutics is a discipline or method of interpretation used to understand and interpret texts, especially complex texts such as literature, religious texts, or philosophy. Hermeneutics involves the process of studying texts comprehensively, analyzing the structure of the text, understanding the context, and searching for the meaning contained therein. A mark is a sign used to distinguish a product or service from similar products or services provided by other parties. A trademark is a mark that is registered with the Mark Registration Office and Geographical Indications, which grants an exclusive right to use the mark in business activities. This study examines the hermeneutical view of the GOTO vs GoTo trademark case contained in the Court Decision Number 71/Pdt.Sus-HKI/Merek/2021/PN Niaga Jkt.Pst. The purpose of this study is to find out the protection regarding Trademarks in Indonesia and how the hermeneutical view of the case of the GOTO vs GoTo Trademarks. The research method used in this journal is normative juridical, which is an approach made by examining the principles, theories, concepts, principles, and legislation related to the research problem being studied. The results of this study are that PT TFT has a class and type that is different from Gojek Tokopedia, therefore in the trial the lawsuit against PT TFT was rejected. In this case, hermeneutics or interpretation is also used so that we can find out the existing meaning and the causes of the case.